1999
DOI: 10.1093/emboj/18.24.7077
|View full text |Cite
|
Sign up to set email alerts
|

Aphid transmission of cauliflower mosaic virus requires the viral PIII protein

Abstract: The open reading frame (ORF) III product (PIII) of cauliflower mosaic virus is necessary for the infection cycle but its role is poorly understood. We have used in vitro protein binding ('far Western') assays to demonstrate that PIII interacts with the cauliflower mosaic virus (CaMV) ORF II product (PII), a known aphid transmission factor. Aphid transmission of purified virions of the PII-defective strain CM4-184 was dependent upon added PII, but complementation was efficient only in the presence of PIII, demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 28 publications
(43 reference statements)
0
72
0
Order By: Relevance
“…Previous results (10,14) clearly indicated that P2 bound via P3 to virions constitutes the transmissible complex. We believe that the data presented here enlarge the so far static picture of this complex by giving important insights into dynamics and regulation of its formation with far-reaching consequences for the mode of CaMV transmission by aphids.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previous results (10,14) clearly indicated that P2 bound via P3 to virions constitutes the transmissible complex. We believe that the data presented here enlarge the so far static picture of this complex by giving important insights into dynamics and regulation of its formation with far-reaching consequences for the mode of CaMV transmission by aphids.…”
Section: Discussionmentioning
confidence: 90%
“…2 C and D). When the P2 157m mutant (24), which does not bind P3 in vitro (10), was coexpressed with P3 in Sf9 cells, no such inclusion bodies were observed and P3 remained evenly dispersed throughout the cell (not shown). Thus, our results indicate that a P2:P3 complex exists in Sf9 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a coiled-coil domain promotes the interaction between the PIII and PII proteins of Cauliflower mosaic virus during transmission by vector aphids (Leclerc et al, 1998 ;Leh et al, 1999). Two mutations of the PEBV TpA56 2b protein are known to severely affect nematode transmission of the virus.…”
Section: Tobraviruses Which Include Pea Early-browning Virus (Pebv)mentioning
confidence: 99%